FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN - Hermi Hermi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
The purpose of the Company was established to obtain profits and to improve the shareholders' welfare. Maximizing firm value is very important because the company's goals can be realized. The higher the firm value will be a signal for the market to trust the company's prospects in the long run. The purpose of this study was to determine significant the effect of dividend policy, debt policy, company size, growth opportunity and liquidity to firm value of manufacturing companies listed in the Indonesia Stock Exchange year 2015-2018. This study uses multiple linear regression analysis. The population used is a manufacturing company listed in the Indonesia Stock Exchange year 2015-2018 with a total sample of 160 samples. The results of the study simultaneously show that the variables of dividend policy, debt policy, firm size, growth opportunity and liquidity affect the firm value. The results of the study partially stated that dividend policy and debt policy variables positive effect of the firm value. But, firm size, growth opportunity and liquidity do not effect of the firm values